O naruszaniu normy językowej w nazewnictwie metodycznym w minionym ćwierćwieczu - Fiszbak, Jolanta (Dydaktyka Polonistyczna, 2016)
The article raises the problem of linguistic innovations spreading in the didactic vocabulary. They raise objections among teachers and educators because they are dissonant with the culture of Polish language. Unjustified innovations concern lexis and stylistic patterns, however, they do not interfere with intrasystemic rules of the language. Similar tendencies are characteristic for modern Polish language. However, linguistic innovations in didactics are not their result, which makes this situation very dangerous, as it regards scientific life. Instead at school they lead to infantilisation of didactic process, introducing chaos and information noise.